2003
DOI: 10.1029/2003wr002270
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of benthic fish to the patch dynamics of gravel and sand transport in streams

Abstract: [1] Barbel and gudgeon differ in their biology and ecology so that their bioturbation of streambed sediments may have specific effects on the patch dynamics of the sediment transport. Using experimental streams, we tested this idea by measuring the impact of a naturally occurring biomass gradient of each fish on the (1) transport of gravel and sand at base flow; (2) sediment surface characteristics; and (3) critical shear stress (t C ) causing incipient gravel and sand motion during simulated floods. Correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 81 publications
2
52
0
Order By: Relevance
“…Third, it should be noted that our experiment was limited to three fish species, thus neglecting other fish that are known to be active streambed sediments bioturbators either by feeding or swimming (e.g., the barbel Barbus barbus L.1758: Pledger et al, 2014; the gudgeon Gobio gobio L.1758: Statzner et al, 2003b;Statzner and Sagnes, 2008;larval lamprey: Shirakawa et al, 2013) or nest digging (e.g., salmonids: De Vries, 2012), but also other zoogeomorphic animals such as crayfish (e.g., Statzner et al, 2000) or benthic macro-invertebrates (e.g., De Nadaı¨- Monoury et al, 2013). Moreover, due to limited space, a single fish was placed into each aquarium preventing all complex biotic interactions known to affect bioturbating activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it should be noted that our experiment was limited to three fish species, thus neglecting other fish that are known to be active streambed sediments bioturbators either by feeding or swimming (e.g., the barbel Barbus barbus L.1758: Pledger et al, 2014; the gudgeon Gobio gobio L.1758: Statzner et al, 2003b;Statzner and Sagnes, 2008;larval lamprey: Shirakawa et al, 2013) or nest digging (e.g., salmonids: De Vries, 2012), but also other zoogeomorphic animals such as crayfish (e.g., Statzner et al, 2000) or benthic macro-invertebrates (e.g., De Nadaı¨- Monoury et al, 2013). Moreover, due to limited space, a single fish was placed into each aquarium preventing all complex biotic interactions known to affect bioturbating activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that B. barbatula tended to dig more patches that were larger on average than the other two species for which the small number and size of patches disturbed were similar. Several activities may generate SSD by fish such as: (i) foraging activity with the ingestion, digestion and excretion of sediment into the water column (Flecker, 1997;Statzner et al, 2003b;Pledger et al, 2014); (ii) displacement of fine particulate matter (Zhang et al, 2004); (iii) burrowing activity (Shirakawa et al, 2013); (iv) nest digging (Moore, 2006); or (v) swimming activity near the substratum (personal observation). In our study, fish observations conducted during the experiments have enabled us to highlight that SSD was mainly due both to foraging and swimming near the sediment surface.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to foraging, Statzner et al (2003b) and Statzner and Sagnes (2008) have shown that biotic controls (specifically between-species interactions and shoaling, respectively) are relevant in this regard.…”
Section: ; and Other Benthic Feeders Such As Bream Abramis Brama Tenmentioning
confidence: 99%
“…First, Statzner et al (2003b) used ex-situ experiments in small (0.2-m-wide) outdoor channels to investigate the impact of juvenile Barbel Barbus barbus on unstructured, fine gravel beds. They measured a decrease in the critical shear stress (for gravel entrainment) of ~45% as the number of fish that were allowed to forage the bed was increased from zero to eight (Statzner et al, 2003b).…”
Section: ; and Other Benthic Feeders Such As Bream Abramis Brama Tenmentioning
confidence: 99%
See 1 more Smart Citation